Management and long‐term consequences of portal vein thrombosis after liver transplantation in children. Issue 3 (11th March 2013) - Jensen, M. Kyle; Campbell, Kathleen M.; Alonso, Maria H.; Nathan, Jaimie D.; Ryckman, Frederick C.; Tiao, Greg M.
<x xml:space="preserve">Abstract</x> Portal vein thrombosis (PVT) occurs in ≤12% of pediatric recipients of liver transplantation (LT). Known complications of PVT include portal hypertension, allograft loss, and mortality. The management of PVT is varied. A single‐center, case‐control study of pediatric LT recipients with portal vein (PV) changes after LT was performed. Cases were categorized as early PVT (if PVT was detected within 30 days of transplantation) or late PVT (if PVT was detected more than 30 days after transplantation or if early PVT persisted beyond 30 days). Two non‐PVT control patients were matched on the basis of the recipient weight, transplant indication, and allograft type to each patient with PVT. Thirty‐two of the 415 LT recipients (7.7%) received 37 allografts and developed PVT. In comparison with control patients, a higher proportion of patients with PVT had PVT present before LT (13.3% versus 0%, P = 0.01). Patients with early PVT usually returned to the operating room, and 9 of 15 patients (60%) had PV flow restored. Patients with late PVT had lower white blood cell (4.9 [1000/μL] versus 6.8 [1000/μL], P < 0.01) and platelet counts (140 [1000/μL] versus 259 [1000/μL], P < 0.01), an elevated international normalized ratio (1.2 versus 1.0, P < 0.001), and more gastrointestinal bleeding (25% versus 8.3%, P = 0.03) compared to controls. Patients with PVT were also less frequently at the expected grade level (52% versus 88%, P < 0.001). The patient survival rates were 84%, 78%, and 78% and 91%, 84%, and 79% for cases and controls at 1, 5, and 10 years, respectively. The allograft survival rates were 90%, 80%, and 80% for cases and 94%, 89%, and 87% for controls at 1, 5, and 10 years, respectively. In conclusion, patients with early and late PVT had preserved allograft function, and there was no impact on mortality. Patients diagnosed with early PVT often underwent operative interventions with successful restoration of flow. Patients diagnosed with late PVT experienced variceal bleeding, and some required portosystemic shunting procedures. Academic delays were also more common. In late PVT, the clinical presentation dictates care because the optimal management algorithm has not yet been determined. Multi‐institutional studies are needed to confirm these findings and improve patient outcomes. Liver Transpl 19:315–321, 2013. © 2013 AASLD.